Inequality and water pollution in India - Sulhi Ridzuan (IWA Publishing, 2021)
India is notorious for high inequality and high water pollution. There is a growing body of literature that says inequality is harmful to the environment, but it does not receive strong empirical support. We discuss some econometric problems that may have caused mixed findings in the empirical literature and use appropriate tools to overcome the problems. Our empirical results using Indian time-series data show (i) that inequality leads to an increase in water pollution, (ii) that the magnitude of inequality is nearly as large as that of corruption, suggesting that reducing inequality is almost as important as curbing corruption in addressing water pollution challenges in India, and (iii) that increases in water pollution, in turn, widen inequality in India. Our results are robust to various sensitivity checks. We also find no evidence of the environmental Kuznets curve hypothesis for water pollution in India. HIGHLIGHTS We examine the relationship between inequality and water pollution in India and take into account econometric issues in the literature.; We find that inequality leads to an increase in water pollution and the magnitude of inequality is nearly as large as that of corruption.; Increases in water pollution, in turn, widen inequality in India.;